DETERMINAN STUNTING PADA BALITA USIA 25-59 BULAN DI KECAMATAN JAMBI TIMUR - Diana Astuti; Dyah Suryani; Sunarti Sunarti (Bina Generasi : Jurnal Kesehatan, 2023)
Stunting is one of the nutritional problems experienced by toddlers. Stunting can cause the risk of non-communicable diseases in toddlers and impaired brain development. The prevalence of stunting in Indonesia reached 24.4% while the target set by WHO is <20%. The prevalence of stunting in Jambi Province is 22.4%. The incidence of stunting in East Jambi District was 274 cases. This study aims to determine the determinants of stunting in East Jambi District. The design used was cross sectional. The sample of this study were mothers of toddlers who had toddlers aged 25-59 months with a sample size of 105 people. The sampling technique used cluster sampling technique. The research instrument was a questionnaire. Data collection techniques using interview techniques. Data were analyzed using the chi-square test. Based on the results of the study showed that toddlers who experienced stunting amounted to 35.2%. The results of bivariate analysis showed that there was a relationship between knowledge, maternal height, environmental sanitation, birth weight and exclusive breastfeeding with the incidence of stunting (p<0.001). Based on the results of the study, it can be concluded that the incidence of stunting is related to knowledge, maternal height, environmental sanitation, birth weight and exclusive breastfeeding. It is hoped that the Puskesmas will provide education to pregnant women during antinatal care visits about nutrition and counseling for high school students in East Jambi District about balanced nutrition.